A Rare Case Report: A Malignant Histiocytic Tumor in the Form of Ovarian Mass - Emsal Pinar Topdagi Yilmaz; Yakup Kumtepe; Yunus Emre Topdagi; Seray Kaya Topdagi (Case Reports in Obstetrics and Gynecology)
Histiocytic cell malignancies are very rare. Hence, the information about this disease in hematology is limited. In this case report, we present a case of malignant histiocytic tumor affecting the ovary of a 40-year-old virgin female. Primary ovarian malignancy was not considered for the patient who was approached as if she had ovarian malignancy, since there was an indication of a mass in the ovary. Therefore, an aggressive surgery was not performed. Since our patient was in the reproductive age, fertility-preserving surgery was performed. Our patient was then treated systemically by medical oncology. In conclusion, the rare malignancy group was investigated in the present study along with an evaluation of the current literature.